Les graffiti figuratifs, moyen d’appréhender l’identité des prisonniers de la fin du Moyen Âge - Audrey Ségard (Frontière·s)
Among the men of the Middle Ages who have been reduced to anonymity due to an absence or lack of written and archaeological sources, as well as a failure of memory, are the majority of those sentenced to prison. The few archival documents that have come down to us reveal the faces of these unknown men, some of whom were judged by the ecclesiastical justice system, which was known as the officiality. The most that can be ascertained from the few surviving records are the names and dates of detention of the prisoners. In order to recover their identity, it is necessary to study the figurative graffiti, which provides invaluable information. Some prisoners left traces of their passage by “inserting their own images”, in the form of drawings or carvings, on their cell walls. This article will attempt to analyse the means of figurative expression in the late-medieval prison environment, to make them meaningful, to account for the sociocultural practices of those men and to grasp their unveiled identity. In order to gain insight into the concerns, beliefs, thoughts and very life of those men, the figurative graffiti of Selles Castle in Cambrai (France) will be used as an illustration. The Selles Castle served as a confined space in the late Middle Ages, particularly for the Cambrai officiality.